Tick-borne pathogens in raccoons (Procyon lotor) from Germany - Heyse, Lara M.I.; Król, Nina; Rentería-Solís, Zaida; Langner, Torsten; Reinhardt, Nico P.; Pfeffer, Martin; Birka, Stefan; Sebastian, Patrick; Obiegala, Anna (Elsevier, 2025)
Germany is harbouring the majority of Europe's raccoon population, which are considered as invasive neozoa. Many zoonotic pathogens are found in wild raccoons worldwide, but there is a lack of eco-epidemiological data for most of Germany's raccoon populations concerning tick-borne pathogens (TBPs). This is why tissue samples of 485 free-ranging raccoons originating from ten federal states of Germany between the years of 2017 and 2021 were examined for the presence of five TBPs (Borrelia burgdorferi sensu lato, Rickettsia spp., Bartonella spp., Babesia spp. and Neoehrlichia mikurensis) with zoonotic relevance using molecular methods. Borrelia burgdorferi sensu lato was detected in 21 (6.3 %) raccoons, Rickettsia spp. were found in 26 (7.8 %) and Bartonella spp. in 3 (0.6 %) raccoons. Babesia spp. and Neoehrlichia mikurensis were not detected.